Decorated handles in hispanic terra sigillata from the La Cereceda workshop (Arenzana de Arriba, La Rioja) (Salduie, 2022)
We present two new trullae handles (shape H.81) made in Hispanic terra sigillata manufactured in the Flavian era from the La Cereceda workshop (Arenzana de Arriba) belonging to the Tritium pottery center. With these specimens we expand the number of decorated handles, which is quite limited in hispanic productions. Both handles present an exceptional decoration without known parallels that we relate to mythological themes such as the story of Apollo and Daphne, or divinities such as Minerva.
Keywords: Tritium; Roman pottery; Sigillata; Patera; Saucepan; Trulla